Comparing the Robustness of PAYG Pension Schemes - Fall, Falilou (OECD Publishing, 2014)
This paper provides a framework for comparing a defined benefit (DB) and a defined contribution (DC) point schemes, which are both pay-as-you go (PAYG) financed. Two stylised PAYG pension schemes are modelled and simulated to compare their robustness to shocks. The same demographic developments (distribution of workers by age and revenue and distribution of survival rate by age) are applied to the two schemes. The impacts of different shocks (productivity, migration and longevity) on the two schemes are compared. Different policy reforms (increasing the contribution rate, diminishing the pension benefit, changing the up-rating and increasing the retirement age) to cope with the ageing shock are analysed and compared
Keywords: Social Issues/Migration/Health; Economics